Mental Fatigue and Executive Dysfunction in Patients with Cushing’s Syndrome in Remission - Eleni Papakokkinou; Birgitta Johansson; Peter Berglund; Oskar Ragnarsson (Behavioural Neurology)
Patients with Cushing’s syndrome (CS) in remission often suffer from impaired quality of life and cognitive dysfunction. The primary aim was to investigate the occurrence of mental fatigue, characterized by mental exhaustion and long recovery time following mentally strenuous tasks, in patients with CS in remission. The secondary aim was to examine whether the newly developed parts C and D of the trail making test (TMT) are more sensitive, compared to the conventional parts A and B, to evaluate attention and executive function. This was a cross-sectional study including 51 patients with CS in remission and 51 controls. All subjects completed the self-administrated mental fatigue scale (MFS) and performed all four parts of the TMT. The patients had worse outcome on all components of the MFS except for sensitivity to noise. After adjustment for mental fatigue, depression, and anxiety, the patients performed worse only on part D of the TMT (P<0.05). Mental fatigue is common in patients with CS in remission and can be captured by using the MFS. The most demanding part of the TMT, part D, is more useful to capture cognitive deficits in patients with CS in remission compared to the conventional parts A and B.